Regenerative Value Creation - Paździor, Kacper (Regeneratywne tworzenie wartości, 2024)
The urgent issue of climate change and business responsibilities to address has dominated the last decade. Consequently, RVC (Regenerative Value Creation) and SVC (Sustainable Value Creation) were developed as a means of addressing those matters. To investigate the problems of companies responsibilities through the means of R/SVC, comparative method, document analysis method and interview method were used. This study examines the RVC concept, starting with its origins as CSR and going through its implications and execution of businesses of assorted sizes. By bringing up SVC, this study aims to make clear that while RVC is not yet perfect for everyone, it does offer fresh perspectives on corporate and management sociocultural duties. It is argued that RVC is a more progressive and more advantageous strategy for the future, even though SVC is safer and better researched at the moment. Most importantly, it works best when thoroughly thought through and put into practice.
Paździor, K. (2024). Regenerative Value Creation. In D. Teneta (Eds.), Zrównoważony rozwój – trendy, wyzwania, kontrowersje (pp. 124-137). Publishing House of Wroclaw University of Economics and Business.
Keywords: sustainable development; regenerative value creation; zrównoważony rozwój; regeneratywne tworzenie wartości; zrównoważone tworzenie wartości; gospodarka regeneratywna; tworzenie wartości